Toxoplasma gondii Modulates the Host Cell Responses: An Overview of Apoptosis Pathways. (4th April 2019) - Mammari, Nour; Halabi, Mohamad Adnan; Yaacoub, Souha; Chlala, Hilda; Dardé, Marie-Laure; Courtioux, Bertrand
Abstract : Infection with Toxoplasma gondii has a major implication in public health. Toxoplasma gondii is an obligate intracellular protozoan parasite that can infect all nucleated cells belonging to a wide range of host species. One of the particularities of this parasite is its invasion and persistence in host cells of immunocompetent people. This infection is usually asymptomatic. In immunocompromised patients, the infection is severe and symptomatic. The mechanisms by which T. gondii persists are poorly studied in humans. In mouse models, many aspects of the interaction between the parasite and the host cells are being studied. Apoptosis is one of these mechanisms that could be modulated by Toxoplasma to persist in host cells. Indeed, Toxoplasma has often been implicated in the regulation of apoptosis and viability mechanisms in both human and murine infection models. Several of these studies centered on the regulation of apoptosis pathways have revealed interference of this parasite with host cell immunity, cell signalling, and invasion mechanisms. This review provides an overview of recent studies concerning the effect of Toxoplasma on different apoptotic pathways in infected host cells.